The garbage can model of organizational choice looking forward at forty - Lomi, Alessandro, 1961-; Harrison, J. Richard (Emerald, 2012)
The year 2012 is the 40th anniversary of the publication of Cohen, March, and Olsen's influential article "The Garbage Can Model of Organizational Choice", which offered a major new perspective on organizational decision making. To celebrate this enduring paradigm, its impact on our understanding of organizational decision making, and the broad streams of research it has influenced, this collection of papers provides a rich demonstration of the influence that the GCM is continuing to have on current research. The chapters make original contributions to research on organizational decision making by developing new models and theoretical extensions based on or inspired by prior garbage can work, by applying garbage can concepts and interpretations to new problems and novel settings. The year 2012 is the 40th anniversary of the publication of Cohen, March, and Olsen's influential article "The Garbage Can Model of Organizational Choice", which offered a major new perspective on organizational decision making. To celebrate this enduring paradigm, its impact on our understanding of organizational decision making, and the broad streams of research it has influenced, this collection of papers provides a rich demonstration of the influence that the GCM is continuing to have on current research. The chapters make original contributions to research on organizational decision making by developing new models and theoretical extensions based on or inspired by prior garbage can work, by applying garbage can concepts and interpretations to new problems and novel settings. The book includes a paper from Cohen, March and Olsen, who record their memories of initial encounters with garbage can ideas of organizational decision making, impressions of their current condition, and some thoughts on convolutions they may experience in the years ahead.
Keywords: Organizational sociology.; Social sciences.; elektronické knihy; electronic books